2020
DOI: 10.3389/fbioe.2020.585896
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Advances in Antemortem Diagnosis of Human Transmissible Spongiform Encephalopathies

Abstract: Transmissible spongiform encephalopathies (TSEs), also known as prion diseases, arise from the structural conversion of the monomeric, cellular prion protein (PrP C ) into its multimeric scrapie form (PrP Sc ). These pathologies comprise a group of intractable, rapidly evolving neurodegenerative diseases. Currently, a definitive diagnosis of TSE relies on the detection of PrP Sc and/or the identification of pathognomonic histological features in brain tissue samples, which are usually obtained postmortem or, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 214 publications
(269 reference statements)
0
17
0
Order By: Relevance
“…World Health Organization criteria date from 2003. Therefore, they do not include analyses that have improved and developed the criteria after that date [ 247 ].…”
Section: Viruses Commonly Associated With Cns Infection In Brazilmentioning
confidence: 99%
See 2 more Smart Citations
“…World Health Organization criteria date from 2003. Therefore, they do not include analyses that have improved and developed the criteria after that date [ 247 ].…”
Section: Viruses Commonly Associated With Cns Infection In Brazilmentioning
confidence: 99%
“…To classify as a probable or possible TSE, evaluation of symptoms is highly important, but is not sufficient in isolation. Paraclinical tests are essential for the classification of cases and the distinction of other treatable pathologies with similar symptoms [ 247 ]. Table 2 indicates the diagnostic criteria for sCJD classification according to the CDC [ 248 ].…”
Section: Viruses Commonly Associated With Cns Infection In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…Other surrogate markers of neurodegeneration may be helpful in a diagnostic workup, but have varying sensitivities and specificities for prion disease [ 72 ], as listed in Table 2 . Neuron specific enolase (NSE), a marker of brain cell death, is also elevated in acute stroke.…”
Section: Markers For Rapid Neurodegenerationmentioning
confidence: 99%
“…Detection of abnormal aggregated α-syn in CSF of DLB patients by the RT-QuIC assay was first reported by Fairfoul et al (2016) ; this was followed by multiple clinical studies. At present, diagnostic methods using skin ( Orru et al, 2017 ) or OM ( Orru et al, 2014 ; Bongianni et al, 2017 ), which includes CSF, have been reported ( Satoh et al, 2017 ; Ascari et al, 2020 ; Candelise et al, 2020 ).…”
Section: α-Synuclein and Real-time Quaking-induced Conversionmentioning
confidence: 99%